Personalized and targeted therapy of esophageal squamous cell carcinoma: an update. Issue 1 (11th July 2016) - Liu, Yongjing; Xiong, Zhaohui; Beasley, Andrea; D'Amico, Thomas; Chen, Xiaoxin Luke
Abstract : Esophageal squamous cell carcinoma (ESCC) is a deadly disease that requires extensive research. In this review, we update recent progress in the research area of targeted therapy for ESCC. SOX2 and its associated proteins (e.g., ΔNP63α), which regulate lineage survival of ESCC cells, are proposed as therapeutic targets. It is believed that targeting the lineage‐survival mechanism may be more effective than targeting other mechanisms. With the advent of a new era of personalized targeted therapy, there is a need to move from the tumor‐centric model into an organismic model.